Quality of Health Services Before and During the Covid-19 Pandemic In Public Health Center - Menap, Menap; Harmaen, Harmaen; Sastrawan, Sastrawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
Performance evaluation of public health centers must be carried out to measure the level of achievement of quality performance based on customer perspectives and internal service processes. This study aims to evaluate the quality of outpatient services before and during the Covid-19 pandemic at the Aik Darek public health center, West Nusa Tenggara - Indonesia. This study is an exploratory research with comparative descriptive method. A total of 88 research samples were used based on files from outpatients who had visited before the Covid-19 pandemic (October to December 2019) and during the Covid-19 pandemic (March to May 2020). The instrument of this research is a questionnaire from 5 aspects of service quality, tangible, reliability, responsiveness, assurance, and empathy. Descriptive and statistical analyzes were conducted to compare service conditions based on established indicators. The results of this study clearly illustrate that the quality of service before the COVID-19 pandemic was better than during the Pandemic. Satisfaction on the tangible aspect is the most prominent compared to other aspects. The results of statistical analysis also showed significant differences in the two health care conditions based on the five aspects measured. Further description is presented in this article.Â